Standards Used by a Clinical and Scientific Endometriosis Center for the Diagnosis and Therapy of Patients with Endometriosis - Burghaus, Stefanie; Hildebrandt, Thomas; Fahlbusch, Christine; Heusinger, Katharina; Antoniadis, Sophia; Lermann, Johannes; Hackl, Janina; Häberle, Lothar; Renner, Stefan P.; Fasching, Peter A.; Beckmann, Matthias W.; Blum, Simon (Geburtshilfe und Frauenheilkunde, 2019)
Endometriosis is one of the most common benign gynecological diseases. The extremely heterogeneous complex of symptoms complicates the diagnosis and treatment of this disease. In most patients, there is a latency period of several years between the first occurrence of symptoms and the definitive diagnosis. This paper aims (1) to evaluate standards for the diagnosis and treatment of patients with (symptoms suspicious for) endometriosis in terms of feasibility, and (2) to assess the potential use of data collected by a certified clinical and scientific endometriosis center to answer scientific questions. Standards for outpatient consultations were developed for a special endometriosis outpatient clinic. Between January 2014 and December 2017, a total of 1715 outpatients with a suspicion of endometriosis presented to this special endometriosis outpatient clinic; the diagnosis and treatment of patients was carried out in accordance with the developed standards. Data of this patient cohort obtained from patient records created during outpatient consultations and from a questionnaire recorded in an Oracle-based database was analyzed. The patient cohort was also compared with another patient cohort who had attended different outpatient clinics and had been diagnosed intraoperatively with endometriosis. 41.8% of patients examined during special outpatient consultations had surgery for suspicion or recurrence of endometriosis. Endometriosis was confirmed in 81.5% of cases. Pain symptoms were the main indication for surgery in 70.1% of cases compared to 45.1% of cases in the comparison group. The structured approach used in the special endometriosis outpatient clinic is a key aspect of the care provided by the certified clinical and scientific endometriosis center. It ensures that patients are diagnosed and treated in accordance with guideline recommendations, that diagnosis and treatment comply with certification requirements, and that the collected data can be used to answer scientific questions.Endometriose zählt zu den häufigsten gutartigen gynäkologischen Erkrankungen. Ein sehr heterogener Symptomkomplex erschwert die Diagnose und die Therapie der Erkrankung. Meist besteht eine mehrjährige Latenz zwischen dem erstmaligen Auftreten von Symptomen und der Diagnosestellung. Ziel der vorliegenden Arbeit sind (1) die Überprüfung von definierten Standards für die Diagnostik und die Therapie von Patientinnen mit (Verdacht auf) Endometriose auf ihre Umsetzbarkeit und (2) eine mögliche Nutzung dieses zur Beantwortung von wissenschaftlichen Fragestellungen als Grundlage im zertifizierten klinischen und wissenschaftlichen Endometriosezentrum. In der Spezialambulanz für Endometriose wurde ein Standard für die Durchführung dieser Sprechstunde entwickelt. Im Rahmen dieser Spezialambulanz erfolgten 1715 ambulante Patientenvorstellungen von Januar 2014 bis Dezember 2017, wegen der (Verdachts-)Diagnose Endometriose, die nach diesem Standard diagnostiziert und behandelt wurden. Anhand der Dokumentation der Patientinnenakte und des Fragebogens in einer Oracle-basierten Datenbank wurde eine Analyse des aus dieser Sprechstunde hervorgehenden Patientenkollektivs durchgeführt. Zudem wurde ein Vergleich mit dem Patientinnenkollektiv durchgeführt, das sich in anderen Spezialambulanzen vorgestellt hat und bei dem intraoperativ ebenfalls Endometriose diagnostiziert wurde. 41,8% der Patientinnen aus dieser Sprechstunde wurden bei Verdacht auf Endometriose oder dem Rezidiv einer Endometriose operiert. Eine Endometriose konnte bei 81,5% bestätigt werden. Die Schmerzsymptomatik war in 70,1% die Hauptindikation für die Operation, im Vergleichskollektiv war diese 45,1%. Die vorgestellte Strukturierung einer Spezialambulanz für Endometriose als zentraler Bestandteil eines zertifizierten klinischen und wissenschaftlichen Endometriosezentrums ermöglicht eine leitliniengerechte Diagnostik und Therapie der Patientinnen mit Endometriose, die Erfüllung der Zertifizierungsvoraussetzungen und das Beantworten von wissenschaftlichen Fragestellungen.
Keywords: endometriosis; sterility; lower abdominal pain; diagnostic